Paleoeskimo Demography and Holocene Sea-level History, Gulf of Boothia, Arctic Canada - Dyke, Arthur S.; Savelle, James M.; Johnson, Donald S. (ARCTIC, 2011)
Surveys in six areas along the Gulf of Boothia produced large collections of radiocarbon samples from raised beaches that yield six new relative sea-level curves and information on Holocene bowhead whale ranges. In addition, on the lower beaches, we documented 482 Paleoeskimo dwelling features spanning about 3500 years (4200–800 14C years BP). Spatial densities of sites are only about half those reported by us from adjacent regions, but other attributes are remarkably similar. On the basis of feature elevation, corroborated by radiocarbon dates, Paleoeskimo occupation appears to have passed through a series of boom-and-bust cycles, the first being the most prominent. After the first peopling about 4200 BP, populations rose between about 3900 and 3600 BP to their all-time maximum, which was followed by a dramatic crash. Population recoveries after the initial crash were small and perhaps temporary. A final increase between 1900 (1500) and 800 14C years BP was followed by the disappearance of the Paleoeskimo. No compelling evidence yet points to the cause of the population declines; climate change and resource over-exploitation are equally plausible. The frequency distributions of dwelling sizes and numbers of dwellings per site closely resemble those in adjacent regions, suggesting similar social dynamics. Specifically, dispersed nuclear families or small extended families characterized Paleoeskimo settlement patterns for most of the year, but annual aggregations involved 100 or more people. The only significant architectural change coincides with the arrival of Late Dorset people bringing distinctive triangular midpassages and soapstone lamp supports. Des levés réalisés dans six régions situées le long du golfe de Boothia ont permis de recueillir de vastes collections d’échantillons au carbone 14 provenant de plages surélevées. Les résultats découlant de ces levés produisent six nouvelles résonances relatives du niveau de la mer de même que des renseignements sur le parcours des baleines de l’Holocène. Par ...